1998
DOI: 10.1046/j.1365-2249.1998.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal disease and polymorphism of FcγRIIa (CD32) in late complement component-deficient individuals

Abstract: Late complement component‐deficient (LCCD) individuals lack plasma bactericidal activity and are highly susceptible to meningococcal disease. Phagocytosis plays a significant role in immune defence against meningococci and involves FcγRIIa (CD32) on leucocytes. Two allotypic forms are currently recognized: FcγRIIa‐R131 and RIIa‐H131. Neutrophils with the IIa‐H/H131 allotype are more effective in phagocytosis than IIa‐R/R131. We studied the distributions of IIa‐R131 and IIa‐H131 allotypes among 29 Russian LCCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 22 publications
2
28
2
Order By: Relevance
“…FcγRIIa genotyping was performed as described earlier [7, 8]. The cells of only one donor, A.E.P., were used throughout the study to minimize interassay variations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FcγRIIa genotyping was performed as described earlier [7, 8]. The cells of only one donor, A.E.P., were used throughout the study to minimize interassay variations.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of phagocytosis is less clear. We have demonstrated that both complement-sufficient and complement-deficient individuals, having FcγRIIa-H/H131 allotype of leukocyte FcγRIIa IgG receptor, also had a decreased probability to contract severe meningococcal disease [7, 8]. Because human polymorphonuclear leukocytes (PMNL) bearing FcγRIIa-H/H131 allotype are more effective in IgG2-dependent opsonophagocytosis in vitro and because most anticapsular meningococcal antibodies in vivo belong to IgG2 isotype, these findings suggest that the efficiency of phagocytosis may influence the prevalence and severity of meningococcal disease.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Its role is even more significant in complement deficiency where phagocytosis depends mainly on Fc␥Rs. 10 Understanding the regulation of Fc␥RIIA gene expression in myeloid cells may provide a means for controlling innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have demonstrated higher frequencies of the Fc RIIa-R131/R131 or Fc RIIIb-NA2/NA2 genotypes in patients with meningococcal disease [178][179][180][181][182][183][184] particularly in patients with severe meningococcal disease or fulminant meningococcal septic shock. The Fc RIIa polymorphism has also been demonstrated to be associated with infections due to other encapsulated bacteria [185,186].…”
Section: Fcmentioning
confidence: 99%